(untitled) (European Journal of Economics, Finance and Business Development, 2024)
Competition in the service industry is one of the key points for the success of any enterprise. This work is devoted to the study of current trends in the field of competition and their features in the service sector. The paper considers the main aspects of competition, such as the strengths and weaknesses of competitors, factors that determine the competitive environment, as well as current trends in the field of competition in the service sector. The results of the study showed that today the main trend in the service sector is to increase the level of customer focus of companies, their readiness to quickly and efficiently solve customer problems, as well as to provide innovative services.